Indah di mata - Choh, Patonah Chai (2006)
"Indah di Mata is a poignant and thought-provoking novel that explores themes of identity, cultural conflict, and personal transformation. Set against the rich cultural backdrop of Malaysia, the story delves into the complexities of modern life, family relationships, and the search for self-meaning."
Keywords: Fiction; Fiction; Fiction; Malaysia. -- Fiction; Fiction